2016
DOI: 10.2147/jmdh.s121788
|View full text |Cite
|
Sign up to set email alerts
|

Health provider experiences with galactagogues to support breastfeeding: a cross-sectional survey

Abstract: BackgroundExclusive breastfeeding for infants up to 6 months is widely recommended, yet breastfeeding rates are relatively low in the US. The most common reason women stop breastfeeding early is a perceived insufficiency of milk. Galactagogues are herbal and pharmaceutical products that can help increase milk supply; however, data on their efficacy and safety is limited. Lactation consultants, obstetricians, and other health providers are an important point of contact for breastfeeding women experiencing chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
5
0
2
Order By: Relevance
“…Similarly, about 70% of the healthcare providers reported that they recommend quiet often herbal galactogogues for breastfeeding women seeking recommendations to increase their human milk supply. Our findings were consistent with those previously reported by Bazzano et al in the US, in which 70% of the healthcare providers surveyed indicated that they often recommend galactogogues [ 52 ]. Similarly, fenugreek was the most frequently recommended herbal galactogogue in Bazzano's study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, about 70% of the healthcare providers reported that they recommend quiet often herbal galactogogues for breastfeeding women seeking recommendations to increase their human milk supply. Our findings were consistent with those previously reported by Bazzano et al in the US, in which 70% of the healthcare providers surveyed indicated that they often recommend galactogogues [ 52 ]. Similarly, fenugreek was the most frequently recommended herbal galactogogue in Bazzano's study.…”
Section: Discussionsupporting
confidence: 93%
“…The panel of healthcare providers was composed of gynecologists/obstetricians, pediatricians, family physicians, lactation consultants, and pharmacists. Those healthcare professionals would normally be consulted by breastfeeding women seeking recommendations to increase their human milk supply [ 17 , 52 ]. Women who were recruited for the panel of women experienced inadequate human milk supply sought recommendations from healthcare providers and used herbal galactogogues.…”
Section: Discussionmentioning
confidence: 99%
“…In various regions of the world, several herbs are used to promote lactation, with T. foenum-graecum L. and F. vulgare Mill being the most common ( Forinash et al, 2012 ; Mortel and Mehta, 2013 ; Sim et al, 2013 ; Sim et al, 2014 ; Sim et al, 2015 ; Bazzano et al, 2016 ; Javan et al, 2017 ; Zheng et al, 2020 ). The origin of the two herbs resembles those indicated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There is generally a high-level of market acceptance in the use of galactagogue to increase milk production, as reported in several publications. In general, the topic of research on galactagogue can be categorised into plant only [55][56][57], plant and food [58][59][60], and plant and pharmacological galactagogue [61][62][63]. Although these articles were excluded in our study, the studies have highlighted that many mothers have shown interest and optimism regarding consumption of galactagogue to improve milk production [56].…”
Section: Excluded Studiesmentioning
confidence: 99%